Brownian motion and thermophoresis effects on bioconvection of rotating Maxwell nanofluid over a Riga plate with Arrhenius activation energy and Cattaneo-Christov heat flux theory. (1st June 2021) - Ali, Bagh; Pattnaik, P.K.; Naqvi, Rizwan Ali; Waqas, Hassan; Hussain, Sajjad
Highlights: Rotating flow of Maxwell nanofluid persuaded by Cattaneo Christov diffusion is modeled. Buongiorno model for nanoparticles is taken into account for modeling. The higher values of Brownian motion and thermophoresis boosted the temperature. Binary chemical reaction with novel aspect of activation energy is accounted. The larger modified Hartmaan number reduces the coefficient of skin friction in primary direction. Abstract: The heat and mass transportation for the bioconvection transient rotating flow of Maxwell nanofluid over Riga plate is inspected in the present investigation. The bioconvection is utilized alongside nanofluids to provide stability to improved thermal transportation. Further, Cattano-Christov theory, Buongiorno model, binary chemical reaction, and activation energy are incorporated. The unsteady three dimensional partially differentiate formulation is simplified in the form of two independent coordinates ( ζ, η ) . For steady-state solution ( ζ = 1 ), Glerikin discretization in used to employ finite element simulation in MATLAB environment. The buoyancy ratio parameters, unsteady parameter, rotating parameter, thermophoresis, and Brownian motion parameter escalated the nanofluid temperature field. Modified electromagnetic parameter M H accelerated the primary flow velocity and activation energy augmented the volume fraction of nanoparticles in the boundary layer region. The larger modified Hartmaan number M H reduces the coefficient of skin friction in primary direction but the magnitude of coefficient of skin friction in secondary direction is augmented. The local Nusselt number Re x 1 / 2 Nu x is directly proportional to M H and β 2 but it is inversely related to β 1 and α T .